Controlling Strategies Of Krueng Doy River Water Pollution Of Banda Aceh City - Adi Winata; Edi Munawar; Nasrullah Nasrullah (Journal of Applied Technology, 2022)
This study aims to analyze the quality of river water and also to formulate several pollution control strategies that can be applied in community life in a sustainable manner. Analysis of the water quality of the Krueng Doy River in Banda Aceh City was carried out by comparing it to the Government Regulation of the Republic of Indonesia number 82 of 2001. The method used in this research is to use the SWOT matrix. River water quality in upstream and downstream areas has increased pollution index. SWOT analysis shows that Krueng Doy river management policy is currently in quadrant IV with characteristics of SW and OT, so that the strategy used is "defensive", namely by utilizing opportunities derived from elements of the Government's role and prioritizing policy with (1) river sustainability utilization policy; (2) community education and prevention of waste and waste throughout the river; (3) Decisive action for the perpetrators of pollution against the river environment; and (4) community empowerment and the provision of river management budgets.